Multi-component topology optimization for thin-walled structures. Issue 5 (4th May 2022) - Zhang, Junyuan; Wang, Shihang; Zhou, Hao; Ning, Linan
Abstract : This article presents a multi-component topology optimization method for thin-walled structures, which can be applied to two-dimensional plate components and three-dimensional tube components. Based on the theory of multi-component topology optimization for stamped sheet metal assemblies, an accurate calculation method for the Young's modulus of joint elements is provided. To avoid the discontinuous derivative and improve the optimization efficiency, a non-zero gradient-based material interpolation scheme with penalization is constructed. The cost of die-set materials can be controlled effectively by the maximum size of components. Several topology designs based on minimized compliance confirm the effectiveness of the proposed method. The topology solutions illustrate that the proposed method can realize the structural design of thin-walled structures which can meet the die-set material cost requirement.